2007
DOI: 10.18433/j3kw2z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Chemosensitizing Effects of Flavonoids with Hydroxy and/or Methoxy Groups and Structure-Activity Relationship

Abstract: Purpose. Flavonoids have been used as antioxidant, chemopreventive and chemosensitizing agents. In this study, eleven flavonoids containing a variety of hydroxy (OH) and/or methoxy (OMe) groups were evaluated for their antioxidant, cytotoxic and chemosensitizing effects to create a structure-activity relationship (SAR). Methods. 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical solution-based chemical assay and and 2',7'-dichlorofluorescin diacetate (DCFH-DA) cellular-based assay were used to compare the free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 22 publications
9
51
0
1
Order By: Relevance
“…24) Jeong et al have suggested that flavonoids with 3-OH group play a positive role in antioxidant activities. 25) Thus, it is well known that there are differences in the anti-oxidative revitalization and anti-inflammatory actions according to the structure of the B ring of flavonoids. The observation that these four flavonoids from Brazilian green propolis have a 4Ј-methoxyl group in the B ring is probably related to the antihypertensive activity.…”
Section: Discussionmentioning
confidence: 99%
“…24) Jeong et al have suggested that flavonoids with 3-OH group play a positive role in antioxidant activities. 25) Thus, it is well known that there are differences in the anti-oxidative revitalization and anti-inflammatory actions according to the structure of the B ring of flavonoids. The observation that these four flavonoids from Brazilian green propolis have a 4Ј-methoxyl group in the B ring is probably related to the antihypertensive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Semakin banyak gugus hidroksi pada struktur kimia semakin tinggi aktivitas antioksidan oleh senyawa tersebut (Liu et al, 2010). Sebaliknya, flavonoid yang disubtitusi dengan sejumlah metoksi menunjukkan penurunan aktivitas antioksidan (Jeong et al, 2007). Senyawa diterpen ditandai dengan adanya pita serapan gugus hidroksil pada bilangan gelombang 3500-3480 cm -1 , ester karbonil pada bilangan gelombang 1270-1150 cm -1…”
Section: Penanda Senyawa Antioksidanunclassified
“…Stable free radical scavenging activity Stable free radical scavenging activity was identified using the method reported by Jeong et al [24] . Briefly, 100 μmol/L of DPPH radical solution was dissolved in 100% ethanol.…”
Section: Measurement Of Nitritementioning
confidence: 99%